2009
DOI: 10.5195/ijt.2009.6007
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Telerehabilitation Program: Delivering Early Intervention Services to Rural Families

Abstract: The enTECH Telerehabilitation Program explored the use of telerehabilitation as an alternative service delivery model for early intervention therapy services. Utilizing the Kentucky Telehealth Network, two families living in rural Kentucky received occupational therapy services over a 12-week period. Following program implementation, qualitative data was collected using participant journals and interviews. Data analysis identified three thematic categories related to the program: benefits/strengths, challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 4 publications
2
66
0
10
Order By: Relevance
“…A study by Tindall and Huebner [51] looked at speech therapy delivered by videophones and found that this method alleviated some of the burden of providing care, and produced similar results to face to face consultations. However, the use of digital technology is still limited by educational barriers and socioeconomic status [52,53]. In a recent study of occupational therapists in rural NSW, while the therapists used digital technology for their personal networks and professional development, there was limited use of technology for therapy provision.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Tindall and Huebner [51] looked at speech therapy delivered by videophones and found that this method alleviated some of the burden of providing care, and produced similar results to face to face consultations. However, the use of digital technology is still limited by educational barriers and socioeconomic status [52,53]. In a recent study of occupational therapists in rural NSW, while the therapists used digital technology for their personal networks and professional development, there was limited use of technology for therapy provision.…”
Section: Discussionmentioning
confidence: 98%
“…A handful of telehealth studies examining stakeholder perspectives have been conducted in speech-language pathology for school-aged children [7][8][9][10][11] and occupational therapy early intervention. 12 No studies investigate barriers to communitybased multidisciplinary paediatric allied health telehealth from a multi-stakeholder perspective. Key stakeholders within this context include clients (parents and children), providers (allied health clinicians) and community referrers (eg, schools).…”
Section: Introductionmentioning
confidence: 99%
“…Although the traditional telephone system continues to be a low-cost alternative for effectively conducting interview assessments by various health care professionals (Cooper et al, 2002;Winters, 2002), the proliferation of advanced communication technologies has broadened the possibilities of conducting evaluations using new and more sophisticated technology. Studies have described the use of telerehabilitation in areas that are of concern to occupational therapy such as evaluation and consultative services for wheelchair prescription (Barlow, Liu, & Sekulic, 2009;Schein, Schmeler, Brienza, Saptono, & Parmanto, 2008;Schein, Schmeler, Holm, Saptono, & Brienza, in press), neurological assessment (Savard, Borstad, Tkachuck, Lauderdale, & Conroy, 2003), lower-limb amputation care or ulcer management (Rintala et al, 2004), and early childhood intervention (Cason, 2009;Heimerl & Rasch, 2009). Schmeler, Schein, McCue, & Quetsch.…”
Section: Telerehabilitation In Evaluation and Interventionmentioning
confidence: 99%